A Validated Method for the Detection of Synthetic Cannabinoids in Oral Fluid. Issue 1 (27th July 2018) - Williams, Michelle; Martin, Jennifer; Galettis, Peter
Abstract: Workplace drug testing in Australia is governed by two standards AS/NZS 4308:2008 for testing in urine and AS 4760:2006 for oral fluid. These standards are prescriptive and describe the drugs tested, procedures for analysis and collection devices. However, the drugs listed are not exhaustive and workers may consume novel psychoactive substances without detection. Here we present a validated method for the detection and quantitation of 19 synthetic cannabinoids in oral fluid. These drugs are AM2233, JWH-200, AB-005, AB-FUBINACA, AB-PINACA, AB-CHMINACA, AM2201, RCS-4, JWH-250, STS-135, JWH-73, XLR-11, JWH-251, JWH-18, JWH-122, JWH-19, UR-144, JWH-20 and AKB-48. The sample volume is 100 μL and is subject to a rapid, simple, protein precipitation step prior to centrifugation and injection into the LC–MS/MS system. Chromatographic separation was achieved in 4 min on a Kinetex Biphenyl column (50 mm × 3 mm × 2.6 μm) using 0.1% formic acid in water and acetonitrile as the mobile phase. The method was validated with a limit of detection (1 ng/mL) limit of quantitation (2.5 ng/mL), selectivity, linearity (2.5–500 ng/mL), accuracy (90.5–112.5% of the target concentration) and precision (3–14.7%). This method provides for the rapid detection of synthetic cannabinoids in oral fluid which is readily applicable to a routine laboratory.